Effect of Folic Acid Fortification on Plasma Folate and Total Homocysteine Concentrations - Jacques, P.F; Selhub, J; Bostom, A.G; Wilson, P.W.F; Rosenberg, I.H (The New England journal of medicine, 1999)
Background In 1996, the Food and Drug Administration issued a regulation requiring all enriched grain products to be fortified with folic acid to reduce the risk of neural-tube defects in newborns. Fortification (140 μg per 100 g) began in 1996, and the process was essentially complete by mid-1997. Methods To assess the effect of folic acid fortification on folate status, we measured plasma folate and total homocysteine concentrations (a sensitive marker of folate status) using blood samples from the fifth examination (January 1991 to December 1994) of the Framingham Offspring Study cohort for base-line values and the sixth examination (January 1995 to August 1998) for follow-up values. We divided the cohort into two groups on the basis of the date of their follow-up examination: the study group consisted of 350 subjects who were seen after fortification (September 1997 to March 1998), and the control group consisted of 756 subjects who were seen before fortification (January 1995 to September 1996). Results Among the subjects in the study group who did not use vitamin supplements, the mean folate concentrations increased from 4.6 to 10.0 ng per milliliter (11 to 23 nmol per liter) (P<0.001) from the base-line visit to the follow-up visit, and the prevalence of low folate concentrations (<3 ng per milliliter [7 nmol per liter]) decreased from 22.0 to 1.7 percent (P< 0.001). The mean total homocysteine concentration decreased from 10.1 to 9.4 μmol per liter during this period (P<0.001), and the prevalence of high homocysteine concentrations (>13 μmol per liter) decreased from 18.7 to 9.8 percent (P<0.001). In the control group, there were no statistically significant changes in concentrations of folate or homocysteine. Conclusions The fortification of enriched grain products with folic acid was associated with a substantial improvement in folate status in a population of middle-aged and older adults.